Density Measurements of Negative Hydrogen Ions Using Mass Spectrometer - Abate, Y.; Arciaga, M.; Ramos, H. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
Measurement of negative ion density in a source plasma is necessary for optimizing the extraction of negative ion current. Bacal and co-workers proposed a method to measure the negative ion density by detaching the electron current due to the photodetachment of negative ions using a pulse laser (Bacal et al., 1979). This paper describes a method to determine the negative ion density in a plasma by a coupled mass analysis and Langmuir probe diagnosis of the plasma. The H- ion density was estimated from the relation equating the ratio of the negative ion and electron currents to the ratio of the ion and electron densities; I- / Ic = n- / nc. The proposed estimates consider the collection factor n- / nc.